WOMEN’S REPRESENTATION WITHIN GENDER PERSPECTIVES - Rita Rita; Tri Wahyu Retno Ningsih (University of Muhammadiyah Purwokerto, 2015)
Gender—means a concept, design or value—refers to the system of social relationships that distinguish the functions and roles of women and men because of biological differences or nature. At the same, the society then standardized to 'culture' and as if no longer negotiable, such that it is appropriate for men, while others for women. Various efforts were made to elevate and position of women as equal to men through a variety of institutions, both formal and non-formal. The final goal to be achieved is the realization of gender equality (social justice) in the midst of society. Among the strategies to achieve justice is to involve women in develop-ment. The provision of equal opportunities for women to perform activities in various fields as men appar-ently do not guarantee for the realization of gender equality Keywords: women’s representation, gender, stereotype